Tayangan Televisi dan Perubahan Sosial Masyarakat - Setiawan, Ali Arif (Responsibilitas, 2010)
Abstract Globalization and development of mass information technology especially media broadcasting of television influential to public order. Importance difference between government television stations (TVRI) with station of private sector television orienting at crucible profit aspect had an effect on big to format event of which is presented. One side the side of private sector is more independently in presenting news at the same time public criticism media and opinion to government , side is other affected at individual change, social and local culture good values. Man tends to experiences stress in amused it by media, television especially. Broadcasting media also experiences collision to political importance and power. In the end broadcasting independency non directional and ground floor social public becomes victim conspiracy media and governmental between economic conflict of interests and politics. Public be waiting step of real the role of government of reposition of media to at its(the line as inside information conveyor educates nation do not change social element and public good culture in manipulation of importance as of eye. Keyword: televisi komersial, perubahan masyarakat.